The User Interface, User Experience, and Bakong in Mobile Banking Adoption: A Qualitative Study of Cambodian Users - Ratha Seng; Dr. Rady Chhun; Dr. Seng Tha Chay; Dr. Bunnak Poch (jfpublisher, 2026)
Although prior research on mobile banking adoption has largely relied on quantitative frameworks, limited emphasis has been placed on users’ lived experiences, particularly regarding user interface (UI), user experience (UX), and trust in emerging economies. This qualitative study investigates how UI/UX design features and national digital payment infrastructure influence mobile banking adoption behavior in Cambodia. Semi-structured interviews were conducted with business owners and experienced mobile banking users from diverse sectors, and the data were analyzed thematically to identify recurring patterns.The findings identify four key themes: (1) users show a strong preference for simplicity and functional clarity rather than feature-heavy “super app” designs; (2) UX elements such as transaction confirmations, audio alerts, and clear navigation enhance usability; (3) the Bakong (KHQR) platform supports interoperability and efficient transactions across financial institutions; and (4) users tend to resist complex interfaces, particularly for routine financial activities. Overall, the results suggest that excessive functionality can increase cognitive load and discourage adoption, even among digitally literate individuals.This study contributes to mobile banking and human–computer interaction scholarship by emphasizing the combined influence of UI/UX quality and institutional trust mechanisms on adoption decisions. From a practical standpoint, the findings indicate that financial institutions and fintech developers should prioritize user-centered design, streamlined interfaces, and trust-enhancing functionalities to support sustained mobile banking usage in Cambodia and comparable developing contexts.